Mooi maar goed : Grafisch ontwerpen in Nederland 1987-1998. - Lauwen, Toon; Seinen, Almar (Amsterdam : Stedelijk Museum Amsterdam, 1999)
Hadders, Gerard ; Warmerdam, Matt ; Bos, Peter te ; van Weelden, Esther ; Boot, Studio ; Jongema, Marten ; van Triest, Jaap ; Bons, Jan ; Beeke, Anthon ; Gonnisse en Van Widdershoven ; Hammer, Melle ; Beukers/Scholma ; Van Deursen, Mevis & ; Levie, Victor ; van Bennekom, Jop ; Dumbar, Studio ; van Blokland, Erik ; van Rossum, Just ; Majoor, Martin ; Bierma, Wigger
Mooi maar goed : Grafisch ontwerpen in Nederland 1987-1998, Stedelijk Museum Amsterdam, 15.1.1999 - 28.2.1999
Nederlands
boek
Keywords: Nederland